Managing Virtual Teams: A Qualitative Study at Universitas Triatma Mulya Stenden Bali - ERNA ZULAENI WILES; I Made Bayu Wisnawa; Mark de Jong (Faculty of Business, President University, 2022)
The covid-19 pandemic and the social distancing policy forced Universitas Triatma Mulya Stenden Bali (UTMS) to switch from the conventional team (CT) to a virtual team (VT). The stakeholders were not ready, and references as guidance were nowhere to be found as VT was still new in Indonesia. Once conducted, however, students’ assignments were surprisingly high quality. Students’ evaluations of their education have been higher and more positive. This study was conducted to explore aspects, factors, benefits, challenges, and human resource management (HRM), and to provide recommendations to higher education institutions on how to run a VT. This qualitative research is descriptive-explorative in nature. Interviews were conducted with the Module Coordinators of UTMS, who have experience in conducting CT and VT. Findings show that 1) students are stakeholders, 2) due to its flexibility, efficiency, effectiveness, and profitability, a hybrid team (HT) is considered to be the most ideal and best option for the future, 3) the aspects, the factors and the challenges can be classified into the technology, the people, and the process, aside from leadership, trust, company culture and cultural intelligence, 4) The key success factors of HRM are the sophistication of the technology, class management and virtual presentation skills. To ensure the success of HT, it is recommended that higher education institutions should 1) recruit only experts in the industry, 2) create clear SOPs, 3) provide the right infrastructure and technology, 4) provide training and development programs, 5) give regular 3600 feedback and feedforward, and 6) provide non-financial rewards.